Atopic dermatitis leading to failure to thrive: A case report. Issue 4 (16th May 2022) - Sarver, Melissa M.; Quow, Krystina; Prose, Neil S.
Abstract: We present an infant with severe atopic dermatitis, protein loss, and subsequent failure to thrive. With proper management, the patient's laboratory findings normalized, and he gained weight appropriately. In this report, we highlight the impact that severe atopic dermatitis may have growth and development and review the genetic conditions that can result in a similar clinical presentation.